(untitled) (AIUB Journal of Science and Engineering (AJSE), 2023)
Urban migration is becoming an increasing issue in the cities in Bangladesh. Since the migrants are mostly poverty affected, they have no other opportunity than to move to urban slums, where, there is no decent infrastructure. The high density of built-forms and lack of understanding about ventilation strategies and thermal insulation are some of the reasons for their sufferings during the summer and winter months. The constant need for health treatment, infrastructure repairing, increasing utility bills due to lack of daylight and ventilation are affecting their extremely marginal economic condition. This study investigates existing built-forms, socio-economic assets, and living conditions in a particular slum area, located in Dhaka, Bangladesh; and, suggests some adaptive solutions in the form of minor and affordable interventions to upgrade their infrastructure, mostly focusing on the inclusion of daylight and ventilation by retrofitting the existing condition.